2010
DOI: 10.4028/www.scientific.net/msf.654-656.635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minor Additions of Al and Si on the Mechanical Properties of Cast Mg-3Sn-2Ca Alloys in Low Temperature Range

Abstract: The Mg-Sn-Ca alloys have shown superior creep properties compared to the creep resistant alloy AE42. In the present study, the effects of small amounts of Al and Si additions on the mechanical properties have been investigated on a Mg-3Sn-2Ca (TX32) alloy. The Al content in the selected alloys was 0.4 wt% and the Si content was varied from 0–0.8 wt% in steps of 0.2 wt.%. The alloys were cast in pre-heated permanent molds. Cylindrical specimens machined from the cast billets were tested in compression in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Mg-Sn-Ca (TX) alloys are attractive candidates among Al-free alloys, potentially providing reasonable corrosion and good creep resistance [2][3][4][5]. It was shown that such alloys were able to compete with AZ91 in terms of corrosion behaviour and also showed a dramatic improvement of creep properties, comparable to the creep resistant alloy AE42 [6]. Interesting variations of these TX alloys require knowledge about the impact of other alloying elements such as Si and Ce in the corresponding multicomponent Mg-alloy systems TXS and TXE.…”
Section: Introductionmentioning
confidence: 98%
“…Mg-Sn-Ca (TX) alloys are attractive candidates among Al-free alloys, potentially providing reasonable corrosion and good creep resistance [2][3][4][5]. It was shown that such alloys were able to compete with AZ91 in terms of corrosion behaviour and also showed a dramatic improvement of creep properties, comparable to the creep resistant alloy AE42 [6]. Interesting variations of these TX alloys require knowledge about the impact of other alloying elements such as Si and Ce in the corresponding multicomponent Mg-alloy systems TXS and TXE.…”
Section: Introductionmentioning
confidence: 98%
“…In this series, Mg-3Sn-2Ca (TX32) alloy was found to exhibit a fair balance between the creep resistance and the corrosion resistance [5,7]. An attempt was made to increase the strength of TX32 alloy by adding 0.4 wt % Al [8]. In a view to increase the strength further, 0.4 wt % Zn was also added to Mg-3Sn-2Ca-0.4Al (TX32-0.4Al) alloy.…”
Section: Introductionmentioning
confidence: 99%